Association between internal training load and muscle injuries in Brazilian professional soccer players - Mohr, P. A.; Matias, T. S.; de Lucas, R. (Biology of Sport, 2023)
The training load is associated with injury risk in a variety of sports. This study aimed to evaluate the association between the internal training load and injury risk in Brazilian professional soccer players. The data were collected from 32 soccer players across two full seasons (2017 and 2018). The rating of perceived exertion (RPE) for every training/match session was used as an internal load variable. The cumulative training load from 3 and 4 weeks (C3 and C4) and the acute:chronic workload ratio (ACWR) were calculated. A generalized estimating equation analysis was applied to examine associations of non-contact muscle injuries with C3, C4 and ACWR. A total of 33 injuries were recorded across the two full seasons. A significant association was found between cumulative training load for three (C3, p = 0.003) and four weeks (C4, p = 0.023) and the occurrence of injuries. Players in the "high load" group presented greater injury risk in relation to the "moderate load" group (C4: OR = 4.5; IC 95% 1.5-13.3; C3: OR = 3.7; IC 95% 1.7-8.1). There was no association between ACWR and injury occurrence. The athletes exposed to a high cumulative load in a period of 3 to 4 weeks presented higher injury risk in comparison to those who had moderate cumulative training loads. Besides that, there was no association between ACWR and injury occurrence.